Consumer-oriented (patient and family) outcomes from nursing in genomics: a scoping review of the literature (2012–2022) - Keels, Jordan N.; Thomas, Joanne; Calzone, Kathleen A.; Badzek, Laurie; Dewell, Sarah; Murthy, Vinaya; O’Shea, Rosie; Tonkin, Emma T.; Dwyer, Andrew A. (Frontiers in Genetics, 2024)
IntroductionGenomics is a lifespan competency that is important for improving health outcomes for individuals, families, and communities. Nurses play a key role in genomic healthcare and realizing the potential of the genomic era.MethodsWe aimed to chart the current state of genomics in nursing by conducting a systematic scoping review of the literature in four databases (2012–2022). We categorized included articles using the Cochrane Collaboration outcome domains/sub-domains and identify key topical areas.ResultsOf 8532 retrieved articles, we identified 67 articles on ‘consumer-oriented outcomes’ (patient and family) for analysis. Identified articles primarily centered on themes of genetic testing and screening. Most studies reported non-interventional studies 39/67 (58%) and more than half were from the U.S.A. 34/67 (51%). Six of nine subdomains were reported on. The “patient involvement in care” subdomain was the most commonly reported subdomain (17/67, 25%) while “treatment outcomes” had the fewest reports (5/67, 8%). Overall, consumers (i.e., patients and families) had high satisfaction with nurse-led interventions.DiscussionSynthesizing findings revealed key knowledge gaps and unmet patient informational needs around genetic testing and decision support. There are opportunities for interprofessional collaboration between nursing and genetic counseling to meet the mounting demand for genomic healthcare and develop more person-centered approaches to genetic counseling and decisional support. Findings support the need for interventional studies and enhanced focus on implementation for nurses to improve consumer-oriented outcomes.